2010
DOI: 10.1074/jbc.m109.082800
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for the Recognition of Oxidized Phospholipids in Oxidized Low Density Lipoproteins by Class B Scavenger Receptors CD36 and SR-BI

Abstract: Specific oxidized phospholipids (oxPC CD36 ) accumulate in vivo at sites of oxidative stress and serve as high affinity ligands for scavenger receptors class B (CD36 and SR-BI). Recognition of oxPC CD36 by scavenger receptors plays a role in several pathophysiological processes. The structural basis for the recognition of oxPC CD36 by CD36 and SR-BI is poorly understood. A characteristic feature of oxPC CD36 is an sn-2 acyl group that incorporates a terminal ␥-hydroxy (or oxo)-␣,␤-unsaturated carbonyl. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 15 publications
1
49
0
Order By: Relevance
“…In contrast, our studies with POVPC-exposed macrophages show a prominent increase in several proinfl ammatory cytokines, such as TNF-␣ , IL-6, IL-8, and IL-1 ␤ , that play a central role in infl ammation. Thus, there may by the PAF-receptor, scavenger receptor B-I, or CD36 ( 39,40 ). Thus, changes in the structure of the sn -2 group during metabolism could drastically affect the biological activity of these phospholipids.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, our studies with POVPC-exposed macrophages show a prominent increase in several proinfl ammatory cytokines, such as TNF-␣ , IL-6, IL-8, and IL-1 ␤ , that play a central role in infl ammation. Thus, there may by the PAF-receptor, scavenger receptor B-I, or CD36 ( 39,40 ). Thus, changes in the structure of the sn -2 group during metabolism could drastically affect the biological activity of these phospholipids.…”
Section: Discussionmentioning
confidence: 99%
“…All the products were purified by silica gel chromatography and were subjected to 1 H-and 13 C-nuclear magnetic resonance spectrometry and gas chromatograph-mass spectrometry for quality assessment. On the basis of gas chromatography, the puriimportant for interactions with the binding site (5). Recently, we and others have demonstrated that CD36 is produced by distinct types of olfactory sensory neurons and is abundantly present on the surface of the olfactory epithelium (i.e., on the ciliary layer) in mice (14,18,31).…”
Section: Preparation Of Test Compoundsmentioning
confidence: 99%
“…Furthermore, recent data suggest that CD36 is one of the most important receptors associated with bacterial uptake, bacterial endotoxic cellular cytotoxicity (28), and acute and chronic kidney injury (28,(55)(56)(57). These recent data suggest that the vicious cycles of pathogen associated molecular pattern-induced inflammation and DAMP-induced tissue damage may well be mediated through CD36 (58,59). At the same time, independently of the specific mechanisms affecting lung inflammation, SAHPs are important tools that decrease pulmonary damage induced by proinflammatory compounds (51,60).…”
Section: Discussionmentioning
confidence: 99%